Study on the molecular mechanism of UBA52 and BARD1 regulating hepatocellular carcinoma through the PI3 K/AKT signaling pathway - Chenrui Yang; Yanzhong Zhang; Yajuan Liu; Xiaoyong Wu; Fangyuan Sun (Discover Oncology)
Abstract Background Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related deaths globally, with its development closely related to complex molecular mechanisms such as gene mutations and abnormal signaling pathways. However, the specific roles of many key genes remain unclear. UBA52 and BARD1 are important genes associated with protein degradation, DNA repair, and cell cycle regulation, but their mechanisms in liver cancer are not well understood. Methods This study integrated HCC datasets (GSE135631, GSE184733, GSE202853) from the gene expression omnibus (GEO) database to screen for differentially expressed genes (DEGs), perform functional enrichment analysis, weighted gene co-expression network analysis (WGCNA), construct protein–protein interaction (PPI) networks, and conduct survival analysis. Western Blot (WB) and RT-qPCR experiments were used to verify the expression of UBA52 and BARD1 in liver cancer cells and their association with the PI3K/AKT signaling pathway. Results Bioinformatics analysis identified UBA52 and BARD1 as core genes, showing high expression in HCC tissues and correlation with poor prognosis. Western Blot and RT-qPCR results further confirmed the high expression of UBA52 and BARD1 in HCC cell lines (HepG2 and Hep3b). PI3K inhibitors significantly downregulated the expression of UBA52 and BARD1, restored the levels of apoptosis-related factors (Fas, BAX, Caspase-3), and inhibited the expression of cell cycle-related proteins (Cyclin-D1, c-Myc). These findings suggest that UBA52 and BARD1 may regulate HCC cell proliferation, apoptosis, and metastasis through the PI3K/AKT signaling pathway. Furthermore, the molecular mechanism of hepatocellular carcinoma can be modulated by knocking out BARD1 or UBA52. Conclusion UBA52 and BARD1 are highly expressed in HCC, and their abnormal expression may promote the occurrence and development of liver cancer by regulating the PI3K/AKT signaling pathway and mechanisms related to apoptosis and cell cycle. The high expression of UBA52 and BARD1 is closely associated with poor prognosis, indicating their potential value as early diagnostic and targeted therapeutic biomarkers for HCC.